2020
DOI: 10.3389/fpubh.2020.00312
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Female Community Health Volunteer Capacity Building and Text Messaging Intervention on Gestational Weight Gain and Hemoglobin Change Among Pregnant Women in Southern Nepal: A Cluster Randomized Controlled Trial

Abstract: Conclusions: The study shows that FCHV capacity building and mobile text messaging have a positive effect on the gestational weights and hemoglobin levels of expectant mothers. Our findings suggest that mobile text messaging coupled with FCHV capacity building services should be supported and would usefully expand in resource poor settings. Trial registration: ISRCTN60684155.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
5
0
1
Order By: Relevance
“…Research conducted by (Singh, 2020) also stated that training for cadres needs to be improved and routine. Refreshing knowledge is needed to improve the abilities of individuals, community groups and social institutions in terms of knowledge, skills and behavior through interesting activities for cadres.…”
Section: Discussionmentioning
confidence: 99%
“…Research conducted by (Singh, 2020) also stated that training for cadres needs to be improved and routine. Refreshing knowledge is needed to improve the abilities of individuals, community groups and social institutions in terms of knowledge, skills and behavior through interesting activities for cadres.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its high prevalence, anemia in pregnancy is a common theme that is regularly addressed by many authors in Africa and elsewhere; however, few results of communitybased trials have been published on the specific topic of anemia in pregnancy, and those studies often conclude that there is no effect on the prevalence of anemia. 6,8,9 For example, in a study carried out by Ampofo et al in Ghana in 2018 on the contribution of pregnant women to anemia control, no difference in prevalence was observed at term between the intervention and control groups, due (according to the authors) to the low fidelity of the actors to the implementation of the study protocol. In this study, the intervention occurred only in health facilities, where the counseling that was designed to produce results was offered to pregnant women during a prenatal visit.…”
Section: Discussionmentioning
confidence: 99%
“…There are few randomized community-level trials addressing the effectiveness of these strategies, and these generally target isolated strategies, particularly micronutrient supplementation. 5,6 Recently published cluster trials on the specific topic of anemia in pregnancy include that conducted by Bharti et al in India on the effects of directly observed supervision of iron supplementation and by Ampofo et al in Ghana on the contribution of pregnant women to anemia control. 7,8 In the first case, the intervention reduced the prevalence of anemia by more than half, whereas there was no effect on prevalence in the second trial; however, maternal anemia has often been evaluated through numerous cluster intervention studies of malaria control.…”
Section: Introductionmentioning
confidence: 99%
“…Majority of the studies used text messaging for reminding the pregnant women to take iron tablet regularly (19,21,22,25). Some studies was implementing the intervention for improving maternal and child health through the application and followed by text messaging for supporting the application as reminder to take iron supplementation (19,22) and the others studies was implementing text messaging as reminder along with health education (21,25).…”
Section: Text Messagingmentioning
confidence: 99%